External adjustment of unmeasured confounders in a case–control study of benzodiazepine use and cancer risk - Thygesen, Lau Caspar (Br J Clin Pharmacol, 2017)
AIMS: Previous studies have reported diverging results on the association between benzodiazepine use and cancer risk. METHODS: We investigated this association in a matched case–control study including incident cancer cases during 2002–2009 in the Danish Cancer Registry (n = 94 923) and age‐ and sex‐matched (1:8) population controls (n = 759 334). Long‐term benzodiazepine use was defined as ≥500 defined daily doses 1–5 years prior to the index date. We implemented propensity score (PS) calibration using external information on confounders available from a survey of the Danish population. Two PSs were used: The error‐prone PS using register‐based confounders and the calibrated PS based on both register‐ and survey‐based confounders, retrieved from the Health Interview Survey. RESULTS: Register‐based data showed that cancer cases had more diagnoses, higher comorbidity score and more co‐medication then population controls. Survey‐based data showed lower self‐rated health, more self‐reported diseases, and more smokers as well as subjects with sedentary lifestyle among benzodiazepine users. By PS calibration, the odds ratio for cancer overall associated with benzodiazepine use decreased from 1.16 to 1.09 (95% confidence interval 1.00–1.19) and for smoking‐related cancers from 1.20 to 1.10 (95% confidence interval 1.00–1.21). CONCLUSION: We conclude that the increased risk observed in the solely register‐based study could partly be attributed to unmeasured confounding.